The Long-Term Prognostic Significance of Circulating Tumor Cells in Ovarian Cancer—A Study of the OVCAD Consortium - Obermayr, Eva; Reiner, Angelika; Brandt, Burkhard; Braicu, Elena Ioana; Reinthaller, Alexander; Loverix, Liselore; Concin, Nicole; Woelber, Linn; Mahner, Sven; Sehouli, Jalid; Vergote, Ignace; Zeillinger, Robert (Cancers, 2021)
Introduction: We previously reported the prognostic impact of circulating tumor cells (CTCs) in a multicenter study on minimal residual disease in primary ovarian cancer. With additional follow-up data, we evaluated the combined CTC approach (CTCscombo), in particular for the patients who had survived more than five years. Material and Methods: Blood samples taken at baseline and six months after adjuvant treatment (follow-up) were assessed by quantitative PCR (qPCR) measuring PPIC transcripts and immunofluorescent staining (IF). A positive result with either IF or qPCR was classified as CTCcombo-positive. Further, PPIC was assessed in the primary tumor tissue. Results: The concordance of IF and qPCR was 65% at baseline and 83% after treatment. Results showed that 50.5% of the baseline and 29.5% of the follow-up samples were CTCcombo-positive. CTCscombo after treatment were associated with increased mortality after adjusting for FIGO stage (HR 2.574, 95% CI: 1.227–5.398, p = 0.012), a higher risk of recurrence after adjusting for peritoneal carcinosis (HR 4.068, 95% CI: 1.948–8.498, p < 0.001), and increased mortality after five survived years. Discussion: The two-sided analytical approach revealed CTC subpopulations associated with ovarian cancer progression and may illuminate a potential treatment-related shift in molecular phenotypes. That approach can identify patients who have elevated risk of recurrence and death due to ovarian cancer and who may require risk-adapted treatment strategies.